2017
DOI: 10.1016/j.quaint.2017.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary sea-level changes and early human societies in the central and eastern Mediterranean Basin: An interdisciplinary review

Abstract: This article reviews key data and debates focused on relative sea-level changes since the Last Interglacial\ud (approximately the last 132,000 years) in the Mediterranean Basin, and their implications for past human\ud populations. Geological and geomorphological landscape studies are critical to archaeology. Coastal regions\ud provide a wide range of resources to the populations that inhabit them. Coastal landscapes are\ud increasingly the focus of scholarly discussions from the earliest exploitation of litto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
142
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(149 citation statements)
references
References 273 publications
3
142
0
4
Order By: Relevance
“…Location of the Italian key sites with MIS3 human occupations. The Italian Peninsula shows a sea level of 70 m below the present-day coastline, based on the global sea-level curve (Benjamin et al, 2017) but lacking the estimation of post-MIS3 sedimentary thickness and eustatic magnitude (sketch map courtesy by S. Ricci, University of Siena). del Cavallo, Riparo del Broion) ( Fig.…”
Section: Geographical Distribution Stratigraphies and Chronologymentioning
confidence: 99%
“…Location of the Italian key sites with MIS3 human occupations. The Italian Peninsula shows a sea level of 70 m below the present-day coastline, based on the global sea-level curve (Benjamin et al, 2017) but lacking the estimation of post-MIS3 sedimentary thickness and eustatic magnitude (sketch map courtesy by S. Ricci, University of Siena). del Cavallo, Riparo del Broion) ( Fig.…”
Section: Geographical Distribution Stratigraphies and Chronologymentioning
confidence: 99%
“…Submerged archaeological coastal structures are commonly used as indicators of relative sea level changes (Anzidei et al, ; Flemming, Czartoryska, & Hunter, ; Kolaiti & Mourtzas, ; Lambeck, Anzidei, Antonioli, Benini, & Esposito, ; Morhange et al, ; Pirazzoli, ). Recent studies have confirmed that ancient harbor and coastal structures (e.g., quays and fish tanks) are reliable sea level indicators, as they are directly related to sea level at the time of their construction (Auriemma & Solinas, ; Benjamin et al, ; Evelpidou et al, ; Morhange & Marriner, ; Vacchi et al, ). Rates of local vertical crustal movement can be inferred from the comparison of the current position of the sea level marker, the last usage period or construction time, and the eustatic–isostatic sea level change.…”
Section: Introductionmentioning
confidence: 96%
“…1C). Some of these windows of climatic amelioration coincided with very high sea level, when the crossing of the strait would have required a considerable sea voyage 24 . Prior to the last interglacial, there were three extended intervals of suitably wet climate and low sea level precipitation, from 275k to 242k years ago, from 230k to 221kya, and from 182k to 145kya.…”
mentioning
confidence: 99%